Highly selective filtering power divider using substrate integrated waveguide technique for radar applications - Patel, Yogeshkumar Bhadreshbhai; Patel, Amrutbhai Narshihbhai (International Journal of Reconfigurable and Embedded Systems (IJRES), 2024)
This article exhibits a filtering power divider designed with substrate integrated waveguide (SIW) technique, having the power dividing as well as filtering functionalities. In the design band-pass performance is realized by merging SIW structure having high-pass response and complementary split ring resonator (CSRRs) with parallel tank LC resonant response and the dumbbells shape defected ground structure (DGS) with high out of band rejection characteristics. The anticipated structure serves as both a power divider and a filter, it reduces both the cost and the size of the system. Structure is constructed and tested to confirm the design functionality. The measurement result shows the return loss of -25.94 dB with 3-dB fractional bandwidth of 2.85% at 14 GHz.